2020
DOI: 10.3343/alm.2020.40.6.481
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Risk Factors Associated With 30-Day Mortality in Patients With Pneumonia Caused by Hypervirulent Klebsiella pneumoniae (hvKP)

Abstract: Background Reports on metastatic or invasive infections by hypervirulent Klebsiella pneumoniae (hvKP) have increased recently. However, the effects of its virulence on clinical course and outcomes in pneumonia patients have rarely been addressed. We assessed and compared the clinical features of hvKp and classic K. pneumoniae (cKP) strains isolated from patients with pneumonia caused by K. pneumoniae . We also investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…As an opportunistic pathogen, cKP mainly causes infection in hosts who are immunocompromised, or who have existing barrier breakdown (eg, intravascular devices, an endotracheal tube or surgical wounds). 5 HvKP is best described as a virulent pathogen. Distinguishing characteristics of hvKP include community-acquired infections in healthy individuals of any age, multiple sites of infection and a tendency for metastatic dissemination to various sites (eye, lung, central nervous system).…”
Section: Discussionmentioning
confidence: 99%
“…As an opportunistic pathogen, cKP mainly causes infection in hosts who are immunocompromised, or who have existing barrier breakdown (eg, intravascular devices, an endotracheal tube or surgical wounds). 5 HvKP is best described as a virulent pathogen. Distinguishing characteristics of hvKP include community-acquired infections in healthy individuals of any age, multiple sites of infection and a tendency for metastatic dissemination to various sites (eye, lung, central nervous system).…”
Section: Discussionmentioning
confidence: 99%
“… 23 Similarly, Hwang et al recently reported that the 30-day mortality in patients with cKP pneumonia (26.9%) was higher than that in patients with hvKP pneumonia (17.9%). 32 This might be attributed to patients in the cKP subgroup usually having more and much severe underlying diseases, as well as greater age. Additionally, a higher percentage (43.2% in cKP vs 10.3% in hvKP) of a history of hospitalization in recent 90 days may be partially contributed to the higher mortality in the cKP subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Hypervirulent strains of K. pneumoniae can cause a syndrome of pneumonia with invasive and metastatic infections, such as bacteremia, liver abscess and necrotizing fasciitis, whereas the traditional syndrome is associated with pneumonia, urinary tract infection or infection at abdominal or surgical sites, with ulterior bacteremia [ 60 ].…”
Section: Clinical Entitiesmentioning
confidence: 99%
“…Patients with pneumonia caused by K. pneumoniae , either community-acquired or nosocomial, can have worse outcomes given certain risk factors. Hwang et al reported that patients with bacteremia, altered mental status or respiratory rates over 22 breaths per minute presented higher mortality [ 60 ]. Mortality rates appear to be similar for traditional or hypervirulent clinical syndromes [ 60 ].…”
Section: Clinical Entitiesmentioning
confidence: 99%
See 1 more Smart Citation